Trump : - Trump, Donald (Ballantine Books, 2015)
Here is Trump in action—how he runs his organization and how he runs his life—as he meets the people he needs to meet, chats with family and friends, clashes with enemies, and challenges conventional thinking. But even a maverick plays by rules, and Trump has formulated time-tested guidelines for success. He isolates the common elements in his greatest accomplishments; he shatters myths; he names names, spells out the zeros, and fully reveals the deal-maker’s art. And throughout, Trump talks—really talks—about how he does it. Trump: The Art of the Deal is an unguarded look at the mind of a brilliant entrepreneur—the ultimate read for anyone interested in the man behind the spotlight.